Consumer willingness to pay for fair and sustainable foods: who profits in the agri-food chain? - Evangelia Mouchtaropoulou; Evangelia Mouchtaropoulou; Ioannis Mallidis; Ioannis Mallidis; Marianna Giannaki; Konstantinos Koukaras; Simon Früh; Tamara Ettinger; Amine M. Benmehaia; Adnen Kacem; Lotfi Achour; Andreas Detzel; et al. (Frontiers in Sustainable Food Systems)
Going through an era where sustainability and definitions of fairness have been extended and integrated into the agri-food chain, there is a need to understand, on a multi-dimensional and multinational level, the structure of agri-food value chain revenues and consumers’ intentions regarding necessity foods. The study analyzed 1,020 questionnaires from Algeria, Germany, Greece, Italy, and Tunisia revealing that taste prioritizes brand and packaging. Social networks, including family and friends, significantly influence the purchase of fair products. Furthermore, a choice experiment revealed the consumer preferences around attributes of the olive oil case as local, traditional, or organic, from a family or farmer association, in a glass bottle, purchased in small local shops/markets, typical and/or extensive nutritional labeling and health claims, non-relevant branding, and finally a fair price reflecting the reasonable quality of the olive oil product. Regarding the agri-food value chain, the results highlight the revenue distribution among stakeholders as unequal and unfair from consumer perceptions, with an imperative need for transparency. The study investigates in-depth the multifaceted dimensions of the fairness concept in the food market from a consumer’s perception, showing their willingness to pay for necessities based on fair pricing and sustainable practices.